Analysis of the Need for Pizzaluv-Math Learning Media So that Students Can Easily Learn the Limits of Trigonometric Functions - Rani Darmayanti; Akhsanul In'am; Ani Afifah; Anindita Verliana Ridho'i; Dewi Nurmaltasari (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
This research aims to analyze the need for innovative project-based learning media, namely "Pizzaluv-Math," to facilitate students' understanding of the concept of limits of trigonometric functions. "Pizzaluv-Math" integrates mathematical challenges into the pizza-making process, with each pizza ingredient representing a different aspect of the limits of trigonometric functions. This research uses a mixed methods approach consisting of qualitative and quantitative analysis. At the needs analysis stage, semi-structured interviews and classroom observations were conducted with 50 students and ten mathematics teachers from three high schools. The interviews focused on students' experiences with trigonometric functions and their perceptions of the learning process, while the observations aimed to identify specific areas of difficulty in understanding trigonometric function limits. The results of interviews and observations were analyzed using thematic analysis. After developing the learning media, a trial was carried out using a pre-test, a post-test, and a survey to measure the effectiveness of "Pizzaluv-Math." Quantitative data were analyzed using paired t-tests and descriptive statistics. The findings show that many students need help understanding trigonometric function limits and more exciting and interactive learning media. "Pizzaluv-Math" has proven effective in increasing students' understanding of complex mathematical concepts and significantly contributing to mathematics education.